"Freedom Edition": Considering Sony Pictures and The Interview. Issue 4 (1st October 2016) - Kokas, Aynne; Tryon, Chuck; Gusterson, Hugh; Braun, Joshua
Abstract : Culture Digitally is a community of scholars, originally convened by Tarleton Gillespie (Cornell University) and Hector Postigo (Temple University). With generous support from the National Science Foundation, the group supports scholarly inquiry into new media and cultural production through a wide range of projects and collaborations, including a scholarly blog and periodic workshops. For more information on projects and researchers affiliated with Culture Digitally, visit culturedigitally.org or follow @CultureDig on Twitter. This is the latest in the series of Culture Digitally's "dialogues." On occasion, we invite two or more participants to engage in an intellectual back-and-forth, on a point of interest that emerges from discussions at our meetings, around blog posts, or based on evident, shared interests. In these dialogues, scholars are encouraged to grapple with contemporary issues in media, but to do so quite a bit faster than the glacial pace of publishing typically allows. We imagine them as the digital equivalent of the scholarly exchange of letters between pre-eminent scientists. The thinking is meant to be raw and provocative, a chance for the dialogue participants to prod each other beyond their own certainties. The scholars in this dialogue were convened by Joshua Braun in response to the recent public and media discourse surrounding the security breach at Sony Pictures Entertainment and its film, The Interview.